Cytotoxic T lymphocytes - Griffiths, Gillian (Henry Stewart Talks, 2021)
Cytotoxic T Lymphocytes (CTLs), Mechanism of action of CTLs, CTL and the microenvironment, Cytolytic granules, Perforin and Fas ligand, The role of pioneer microtubules, Familial Haemophagocytic Lymphohistiocytosis (FHL), Controlling CTL killing, The role of actin and actin depletion, CTLs are being harnessed in immunotherapies, Co-stimulatory signals and TCRs, CAR-T cells